(3GdCMcGe aj GdMdGd hGdMQGes - (3jMji Hf GdMSjf Hf GdbGSe Hf EHQGgje GdMSfj GdYdhqj GdQSj, GdeYQha H GdgGOj pEdi GdnMqb, J (B298 (3g` s
(3ChdgG (B:s
(3cJGH GdHjhY s
(3BNQgG (B:s
(3bGd jMji Hf GdMSjf QVi Gddg Yfg hEfeG CNQfG PcQ eG PcQfG ef HYV aVd Bd eMeO (B( (3U (B) (3dfNJe HPcQge GdcJGH ceG EHJOCfG Hge Je GdcJGH s
(3faS GdfSNI ef GdLRA GdChd ef GdcJGH GdecJhH SfI (B571 (3g`s
(3HChdgG hOGNdgG ChQGb bdjdI HNW eZGjQ cJHJ SfI (B1155(3g` EceGdkG ddfSNIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis